Cardiopulmonary exercise testing in heart failure and chronic coronary syndromes: From mechanistic diagnosis to CPET-guided management and prognosis in cardiac rehabilitation - rakhmadhani, irzal; Mayangsari, Veny; Tri Tjahjono, Cholid (Universitas Brawijaya, 2026)
Cardiopulmonary exercise testing (CPET) provides an integrated physiological assessment to explain exercise intolerance at the individual-patient level. By integrating breath-by-breath gas exchange with ECG, blood pressure, and symptom monitoring during graded exertion, CPET helps differentiate impaired oxygen delivery (e.g., limited stroke volume augmentation, chronotropic limitation, or ischemia-limited reserve) from ventilatory inefficiency, pulmonary constraint, peripheral deconditioning, or mixed phenotypes—mechanistic information that is directly actionable in heart failure (HF) and chronic coronary syndromes (CCS). In HF, key CPET variables such as peak oxygen uptake (peak VO₂) and ventilatory efficiency consistently reflect clinical severity and are associated with outcomes, supporting decisions from optimization of guideline-directed medical therapy to advanced care planning in selected patients. In CCS, CPET is particularly useful when symptoms are disproportionate to resting findings, when conventional testing is inconclusive, or when microvascular dysfunction or vasospastic angina is suspected; CPET patterns can help refine the dominant mechanism and individualize cardiac rehabilitation intensity and symptom-limited training thresholds. This review proposes a pragmatic workflow aligned with routine practice: (1) mechanism-based interpretation using a compact CPET panel, (2) translation into management and rehabilitation prescriptions, and (3) prognosis and follow-up supported by serial reassessment. Tables 1–2 translate CPET outputs into practical interpretation and exercise-prescription steps, and Figures 1–2 provide worked visual examples of the trajectories discussed in the text.